Identification of the genes at S and Z reveals the molecular basis and evolution of grass self-incompatibility - Herridge, Rowan; McCourt, Tyler; Jacobs, Jeanne M. E.; Mace, Peter; Brownfield, Lynette; Macknight, Richard (Frontiers in Plant Science, 2022)
Self-incompatibility (SI) is a feature of many flowering plants, whereby self-pollen is recognized and rejected by the stigma. In grasses (Poaceae), the genes controlling this phenomenon have not been fully elucidated. Grasses have a unique two-locus system, in which two independent genetic loci (S and Z) control self-recognition. S and Z are thought to have arisen from an ancient duplication, common to all grasses. With new chromosome-scale genome data, we examined the genes present at S- and Z-loci, firstly in ryegrass (Lolium perenne), and subsequently in ~20 other grass species. We found that two DUF247 genes and a short unstructured protein (SP/ZP) were present at both S- and Z- in all SI species, while in self-compatible species these genes were often lost or mutated. Expression data suggested that DUF247 genes acted as the male components and SP/ZP were the female components. Consistent with their role in distinguishing self- from non-self, all genes were hypervariable, although key secondary structure features were conserved, including the predicted N-terminal cleavage site of SP/ZP. The evolutionary history of these genes was probed, revealing that specificity groups at the Z-locus arose before the advent of various grass subfamilies/species, while specificity groups at the S-locus arose after the split of Panicoideae, Chloridoideae, Oryzoideae and Pooideae. Finally, we propose a model explaining how the proteins encoded at the S and Z loci might function to specify self-incompatibility.